Markers in the polytene chromosomes of freshwater Chironomus Meigen (Diptera, Chironomidae) species - Michailova, Paraskeva (Zootaxa, 2024)
Based on the morphology of the polytene chromosomes, 21 species of the genus Chironomus Meigen from Bulgaria have been identified. Original pictures of the polytene chromosomes are presented for each species. “Basic” sequences were determined for each arm of the polytene chromosomes which are used to determine the corresponding arms of the chromosomes, and the cytocomplex to which the species belongs. The species are distributed in five cytocomplexes: thummi, pseudothummi, parathummi, lacunarius and modified thummi cytocomplexes. Marker sequences have been revealed on chromosome G that are proposed as a species identifier. Cytogenetic characters by which homosequential species of the genus Chironomus can be distinguished are discussed. This study emphasizes the importance of polytene chromosomes for the taxonomy of the species of Chironomus.